Implementation of Maslahah in Islamic Financial Institutions for UMKM Actors in Makassar City: (Case Study of Bank Muamalat Indonesia KCU Makassar) - Amiruddin, Muh Rum Abdau; Paddu, Hamid; Abdireviane, Indraswati Tri (PT. Maju Malaqbi Makkarana, 2023)
Financing is a provider of funding facilities to meet the needs of parties who are deficit units. This research was conducted to analyze the financing system of Bank Muamalat Indonesia KCU Makassar for UMKM actors in Makassar City and to analyze the benefits of UMKM actors in Makassar City through Bank Muamalat Indonesia KCU Makassar financing. The type of research conducted in this research is a type of qualitative research with a sociological-normative approach. The source of the research data is the Muamalat Indonesia KCU Makassar bank. Data collection used interviews and documentation and data analysis techniques used descriptive qualitative analysis and triangulation of data sources. The results of the study show that the procedures for submitting financing to Bank Muamalat Indonesia KCU Makassar prioritize unity, balance, freedom and primarily responsibility. The financing schemes that are often used by Bank Muamalat Indonesia KCU Makassar are mudharabah and musyarakah financing. Benefit can be created by Bank Muamalat Indonesia KCU Makassar for UMKM actors with patterns or implementation of contracts on products that are very much in favor so that the implementation of the benefits of Bank Muamalat Indonesia KCU Makassar has realized in its implementation the financing process for UMKM actors.